The issue of the initial recognition of tennis talents based on the psycho-bodily abilities (psycho-motive and psychological balance) during the process of the initial training of children aged 6-8 years - Katsagolis, A.; Zarotis, G.; Koronas, K.; Mandis, K.; Karagiani, O. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The suitability of young athletes for competitive sports and their athletic orientation are the basic questions which experts have tried to answer (Schmindt, R. 1993, Gould 1987, Singer & Gerson 1978). Many researches have been held by tennis experts (Bos, K. & Wolhmenn, R. 1990, Kohler, K. 1977, Koizner, K. 1987, Katsagolis, A 1992) sup-porting the idea that the natural and empirical choice of young tennis players has to begin at the age 6-8 and the pro-fessional selection after the completion of the 8th year of training. The purpose of this research is the expansion of this situation and the changes of the psycho-bodily abilities and especially the psycho-motive and emotional balance of children aged 6-8 years under the influence of training stimulus during the initial period of learning tennis. On this base we tried to carry out conclusions for the choice and selection of young tennis players. Methods The sample of the research was 120 children of the A` and B` class of primary school. The research was held in two years period. During the period of the research, three athletic- pedagogical tests were carried out (at the beginning, middle and ending of the test). Concerning the dynamic of the psycho-motive and the emotional balance of children, five tests were held. These tests were used to present the intelligent indices, the coordination of movements, the neu-romuscular fitting, the strength (consistency) of the neuromuscular fitting and aggressiveness. Results Based on the results of the tests we conclude that 2 periods of development are defined concerning the psycho-motive and emotional balance of young players. The period from 6 to 7 years old is characterized by a radical devel-opment of the separate indices, and the period from 7 to 8 years is characterized by a more balanced development and the appearance of more complicated abilities. The age under research shows that with the embedment of the movement experience, the important, initial individual differences to the indices of the first period are smoothly dimin-ished, while in the second period is observed a more characteristic tendency towards balance (homogenization) of the psycho-motive ability. Discussion/Conclusion The problem of choice and of athletic orientation has to be faced completely on the basis of the pedagogic, biological psychological, social and other methods of research. The scientific conditions for the determination of the subject of the choice theory has to be searched in the unification of the genotype and the phenotype factor, the biological and the social factor, because every person`s development is determined by the heritage elements as well as the pheno-type which forms it. The peculiarities of the couching system and the athletic-competitive activities, which are connected to the maximum intensity of bodily and psychological abilities, are the objective prerequisite for the athletic selection. The athletic sharpness and the "positive athletic aggressiveness" are elements which have to be studied even further. At the age of 6-8 only predictions can be made without any solid proofs. One reliable methodology for the selection of tennis talents has to be based not only on the techno- athletic and bio-dynamic characteristics but also on the psychological characteristics, taking under consideration the ethnic, personal and emotional peculiarities of the player.